Liquidity risk management in the Portuguese Banking system - Pardal, Ana Teresa Lambiza (2018)
In the light of the recent financial crisis and interbank market turmoil, this study seeks to comprehend the determinants of Portuguese banks’ liquidity management decisions. Based on data from 2005 to 2015, it is found that profitability, efficiency and size are the main drivers of a more aggressive risk-taking policy. Moreover, it is shown that the agent’s optimal strategies relied more significantly on peers’ choices, rather than on own individual fundamental characteristics and performance. Against this background, there is evidence for herding in liquidity management practices in the Portuguese banking industry in the period that preceded the sovereign crisis.